2016
DOI: 10.1021/acs.biochem.6b00355
|View full text |Cite
|
Sign up to set email alerts
|

The Radical S-Adenosyl-l-methionine Enzyme MftC Catalyzes an Oxidative Decarboxylation of the C-Terminus of the MftA Peptide

Abstract: Ribosomally-synthesized post-translationally modified peptides, RiPPs, are encoded in the genomes of a wide variety of microorganisms, in close proximity to orfs that encode enzymes that carry out extensive modifications, many of which are novel. Recently, members of the radical S-adenosyl-l-methionine (SAM) superfamily have been identified in these biosynthetic clusters. Herein we demonstrate the putative radical SAM enzyme, MftC, oxidatively decarboxylates the C-terminus of the MftA peptide in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
80
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(85 citation statements)
references
References 27 publications
4
80
1
Order By: Relevance
“…Members of TIGR03971 appear in gene clusters near mycofactocin system protein genes mftA, mftB, and mftC567. For example, in M. paratuberculosis a putative carveol dehydrogenase (MAP_RS21280, UniProt ID Q73SC8, SSGCID target ID MypaA.01326.b) is encoded near genes for the mycofactocin precursor MftA (MAP_RS21310), the mycofactocin modification chaperone MftB (MAP_RS21315), the mycofactocin radical SAM maturase MftC (MAP_RS21320), the mycofactocin system heme/Flavin oxidoreductase MftD (MAP_RS21325), and the mycofactocin system creatininase family protein (MAP_RS21330).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Members of TIGR03971 appear in gene clusters near mycofactocin system protein genes mftA, mftB, and mftC567. For example, in M. paratuberculosis a putative carveol dehydrogenase (MAP_RS21280, UniProt ID Q73SC8, SSGCID target ID MypaA.01326.b) is encoded near genes for the mycofactocin precursor MftA (MAP_RS21310), the mycofactocin modification chaperone MftB (MAP_RS21315), the mycofactocin radical SAM maturase MftC (MAP_RS21320), the mycofactocin system heme/Flavin oxidoreductase MftD (MAP_RS21325), and the mycofactocin system creatininase family protein (MAP_RS21330).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, the recombinant expression and characterization of MftA, MftB, and MftC have been reported67. The chaperone MftB was reported to bind the mycofactocin precursor MftA with an affinity of approximately 120 nM and the rSAM MftC with an affinity of approximately 2 μM.…”
mentioning
confidence: 99%
“…In the mycofactocin biosynthetic pathway, the peptide chaperone is a stand-alone protein (MftB), and in the thurincin H biosynthetic pathway, the peptide chaperone is fused to the N terminus of the RS protein (ThnB). Although morphologically different, it was shown in both systems that the peptide chaperone protein/domain is required for catalytic turnover by the RS protein (28,29,35). These findings led us to the hypothesis that the PqqD domain is ubiquitous among the remaining characterized RS-SPASM proteins (excluding AnSME).…”
Section: Minireview: Free Radical Enzymology Of Peptidesmentioning
confidence: 99%
“…Mycofactocin is predicted to be a redox cofactor used by a niche set of dehydrogenases found largely in the Mycobacterium genera (26,27). Initially, it was thought that MftC catalyzed the oxidative decarboxylation of the C-terminal tyrosine found on the peptide MftA, resulting in an ␣␤-unsaturated bond (28,29). However, a more detailed mechanistic study demonstrated that the decarboxylated peptide is only an intermediate of a two-step reaction (30).…”
Section: Carbon-carbon Bond Creation: Pqqe Strb and Mftcmentioning
confidence: 99%
“…How are the precursor peptides processed to generate methanobactins (24)? New knowledge about the enzymes involved in other peptide post-translational modifications is becoming available (31,32 (15)? Have all of the accessory proteins for cytochrome oxidase assembly been identified (16)?…”
mentioning
confidence: 99%